Structure of Plankton Communities on The Kalianda Coast, South Lampung - Kusriyati, Kusriyati; Lestari, Septiana Widi; Indrayati, Artin (PELAGICUS, 2024)
The presence of plankton is very important for aquatic ecosystems. Kalianda Coastal Beach has direct access to the open sea. Its water condition can experience changes including physical, chemical, and biological conditions. Moreover, the beaches in the Kalianda coastal area are widely used for vannamei shrimp breeding, ferry port, fishery and trade port. The purpose of this study was to evaluate the structure of the plankton community, including abundance and species composition, diversity index, uniformity, and dominance. This study used data from water sources in three vannamei shrimp nurseries located in Kalianda Coastal Beach, South Lampung. Water parameters observed in Kalianda Coastal were plankton, salinity, pH, nitrate, ammonia, dissolved solids (TSS), and phosphate. The results showed that the plankton found in Kalianda coastal area consisted of four classes, phytoplankton namely Bacillariophyceae (78.75%) and Dynophyceae (9.85%), zooplankton Ciliata (7.79%) and Crustacea (3.61%). The range of phytoplankton abundance is 2392-3029 cells/l, while the abundance of zooplankton is 279-414 ind/l. Plankton diversity and uniformity indices are high meaning that the plankton community in Kalianda Coast is very diverse and stable, low dominance means that there are plankton that dominate, namely from the Bacillariophyceae class. The structure of the plankton community in Kalianda Coastal Beach shows a stable condition at the time of the research. To know the plankton community structure more thoroughly, it is necessary to take plankton samples every season with more station points.